Anti-cancer activities of ω-6 polyunsaturated fatty acids - Yi Xu; Steven Y. Qian (Biomedical Journal, 2014)
The ω-3 and ω-6 polyunsaturated fatty acids (PUFAs) are two major families of PUFAs present as essential cellular components which possess diverse bioactivities. The ω-3s, mainly found in seafood, are associated with many beneficial effects on human health, while the ω-6s are more abundant in our daily diet and could be implicated in many pathological processes including cancer development. Increasing evidence suggests that the adverse effects of ω-6s may be largely attributed to arachidonic acid (AA, a downstream ω-6) and the metabolite prostaglandin E2 (PGE2) that stems from its cyclooxygenase (COX)-catalyzed lipid peroxidation. On the other hand, two of AA's upstream ω-6s, γ-linolenic acid (GLA) and dihomo-γ-linolenic acid (DGLA), are shown to possess certain anti-cancer activities, including inducing cell apoptosis and inhibiting cell proliferation. In this paper, we review the documented anti-cancer activities of ω-6 PUFAs, including the recent findings regarding the anti-cancer effects of free radical-mediated DGLA peroxidation. The possible mechanisms and applications of DGLA (and other ω-6s) in inducing anti-cancer activity are also discussed. Considering the wide availability of ω-6s in our daily diet, the study of the potential beneficial effect of ω-6 PUFAs may guide us to develop an ω-6-based diet care strategy for cancer prevention and treatment.